CP-116 Appropriateness of ticagrelor and prasugrel use after the implementation of an antiplatelet protocol in acute coronary syndrome. (24th March 2015) - Álvaro Alonso, EA; Herrero Domínguez-Berrueta, MDC; Sanz Márquez, S; Collado Borrell, R; Leganés Ramos, A; Pérez Encinas, M
Abstract : Background: Due to the inclusion of new antiplatelet treatment in the pharmacotherapeutic guide, the Cardiology Department developed a protocol for management of antiplatelet treatment in Acute Coronary Syndrome (ACS) in May 2013. Purpose: To check whether the new antiplatelet drugs ticagrelor (T) and prasugrel (P) were being used in accordance with a protocol for managing antiplatelet treatment in ACS. Material and methods: Prospective, observational study of patients receiving T or P. Study period: October 2013–March 2014. In ACS patients with ST-segment elevation (STEACS) the protocol required the location of the myocardial area affected, increased ST visualisation in at least a 3-lead electrocardiogram (ECG), and a score of ≥3 on the TIMI scale. Treatment of patients with non-ST-segment elevation SCA (NST-ACS) required a TIMI score ≥3. Sex, age, weight, presence of diabetes mellitus (DM), history of stroke/transient ischaemic attack (TIA), kidney failure (KF), pharmacotherapeutic history and prior antiplatelet treatment were recorded. A database was created with the variables described. Results: 92 patients were included, 77 males (83.69%), mean age 61.92 ± 10.73 years. 27 patients (29.35%) received ticagrelor and 65 (70.65%) prasugrel. In 12 patients T and P were the usual treatment and they were not considered. Diagnosis: 57/80 (71.25%) STEACS; and 23/80 (28.75%) NST-ACS. Of the 57 patients with STEACS, the infarcted area was anterior/anterolateral in 22 patients, inferior/inferoposterior in 33 and lateral in 2. ST-segment elevation in ≥3 ECG leads (84.21%) was observed in 48 patients. TIMI ≥3 in 44 patients (77.20%). Of the 23 patients with NST-ACS, TIMI score was ≥3 in 20 (86.95%). No patients had stroke/TIA background. However, 18.75% and 1.25% had DM and KF respectively. The total percentage of appropriate use of T and P was 91.25%, reaching 94.55% for P and 84.00% for T. The reasons for non-compliance with the protocol were: in the case of P, not meeting the infarct area (1 patient) or no diagnosis of NST-ACS (1 patient); and in the case of T: no diagnosis of STEACS (2 patients) or NST-ACS with TIMI <3 (1 patient). Conclusion: The use of this management protocol has facilitated both medical prescription and pharmaceutical validation of antiplatelet treatment in patients with ACS. References and/or Acknowledgements: No conflict of interest.